FUNDAMENTALS OF EXTERNAL NETWORK CHARACTERISTICS OF HYDRAULIC SYSTEM - Turdiyev , Sardorjon Abdumuminovich; Akhmedov , Sahib Tojiboyevich (Educational Research in Universal Sciences, 2023)
Nowadays, a number of machines and equipment with a hydraulic system are widely used in mining, construction and agriculture. In order to increase the stable and reliable operation of the hydraulic systems of these machines, it is important to construct the descriptions of their external networks, and the basics of calculating the regulation of hydraulic processes are considered in this article.